Fermented Cashew Apple Beverages: Current State of Knowledge and Prospects - Fabrice S. Codjia; D. Sylvain Dabadé; Pélagie Agbobatinkpo; Ingrid Collombel; Nawel Achir; Paulin Azokpota; Joseph Dossou (Beverages)
The cashew apple constitutes approximately 90% of the total fruit mass produced by the cashew tree, with the remaining 10% being the cashew nut. Despite its high nutritional value, it is regarded as an agricultural byproduct. Numerous scientific studies have explored the technological and nutritional potential of the cashew apple by leveraging microorganisms in its fermentation process for beverage applications. This paper provides an overview of existing fermented cashew apple beverages and discusses perspectives for new fermented cashew apple products. Five fermented cashew apple beverages were recorded. These include wine, edible alcohol, probiotic and prebiotic beverages, and cashew apple-based vinegar. New fermented cashew apple beverages with organoleptic, nutritional, and functional properties can be considered. Among these are fermented cashew apple beverages such as kefir or kombucha-type drinks. A promising avenue for future research is the exploration of the indigenous microbiota of the cashew apple and their interactions within a consortium. This could lead to innovative developments in food technology and improvements in the organoleptic and nutritional characteristics of fermented cashew apple beverages.